(untitled) (Acta Scientiarum. Technology, 2020)
The objective of this study was to analyze the flux-cored arc welding (FCAW) welding parameters and microhardness levels on surface quality of 410 NiMo martensitic stainless-steel coatings. The parameters of the FCAW process applied to the coating, included pulsation frequency, voltage, welding speed, average current and contact tip to work distance. The welding was carried out by the pulsed tubular wire process with pulsed current, constant voltage, Ar+2% O2 shielding gas and short-circuit metal transfer for the deposition of EC410 NiMo Martensitic Steel Deposits alloy coatings on a SAE 1020 steel substrate. For the statistical analysis, the Taguchi experimental planning was applied to test the influence of the parameters of the FCAW process (average current, CTWD, pulsation current and welding speed) on the coating properties. The best configuration with respect to the increased microhardness of the fusion zone in the coating welding process is: Average Current 200 A; CTWD 40 mm; Pulsation Frequency 26.31 Hz and Welding Speed 300 mm min.-1. The lowest microhardness of the melting zone in the coating welding process is: Average Current 170 A; CTWD 30 mm; Pulsation Frequency 23.26 Hz and Welding Speed 400 mm min.-1.